2004
DOI: 10.1111/j.1365-2036.2004.02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Four years of treatment with lamivudine: clinical and virological evaluations in HBe antigen‐negative chronic hepatitis B

Abstract: SUMMARYAim: To evaluate the clinical and virological impact of the prolonged use of lamivudine in 94 patients with HBe antigen-negative chronic hepatitis B. Methods: Initial virological and biochemical responses were obtained in 84 (89%) and in 83 (88%) patients respectively. Results: The virological response peaked within the first 12 months, but diminished to 39% at 48 months because of drug resistance. Overall a virological breakthrough developed in 44 patients (52.4%). After virological breakthrough, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
2
40
1
1
Order By: Relevance
“…Most patients were males (79.7%) and the majority was Caucasians (50.6%) or Asians (48.0%). HCC screening at baseline was reported to be performed in 15 studies including 2807 patients [18,19,21,22,[24][25][26][27]29,32,[34][35][36][37][38] and HCC surveillance during therapy (mostly by alpha-fetoprotein and/or abdominal ultrasound) at least every 6 months in 11 of these studies including 1553 patients [19,21,22,[25][26][27]32,[35][36][37][38], while HCC screening and/or surveillance were not described or performed in the remaining studies (Table 2). It should be noted that the proportion of cirrhotic patients was significantly higher in studies with than without reported strategies for HCC surveillance (650/1553 or 41.9% vs 630/2328 or 27.1%, p < 0.001).…”
Section: Studies and Patient Characteristicsmentioning
confidence: 97%
See 3 more Smart Citations
“…Most patients were males (79.7%) and the majority was Caucasians (50.6%) or Asians (48.0%). HCC screening at baseline was reported to be performed in 15 studies including 2807 patients [18,19,21,22,[24][25][26][27]29,32,[34][35][36][37][38] and HCC surveillance during therapy (mostly by alpha-fetoprotein and/or abdominal ultrasound) at least every 6 months in 11 of these studies including 1553 patients [19,21,22,[25][26][27]32,[35][36][37][38], while HCC screening and/or surveillance were not described or performed in the remaining studies (Table 2). It should be noted that the proportion of cirrhotic patients was significantly higher in studies with than without reported strategies for HCC surveillance (650/1553 or 41.9% vs 630/2328 or 27.1%, p < 0.001).…”
Section: Studies and Patient Characteristicsmentioning
confidence: 97%
“…The mean or median age of the patients was between 30 and 40 years in three studies [18,23,32], between 40 and 50 years in 10 studies [21,22,24,25,29,31,34,[36][37][38] and in the non-cirrhotic patients of one additional study [20], and P50 years in 7 studies [19,[26][27][28]30,33,35] and in the cirrhotic patients of one study [20]. Most patients were males (79.7%) and the majority was Caucasians (50.6%) or Asians (48.0%).…”
Section: Studies and Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymerase gene mutations were observed in 82.5% of virological breakthroughs but also in 75% of the nonresponders [32] . So the mutations outside the YMDD motif in the P protein can independently cause DHBV resistant to Lamivudine is not very strange.…”
mentioning
confidence: 99%